Synthesis and Characterization of an Infrared-blocking Coating for ‎Sustainability Applications (Journal of University of Babylon for Engineering Sciences, 2024)
This study delves into the structural, optical and mechanical properties of polyvinyl alcohol (PVA)-based coatings incorporated with CdS and ZnS nanoparticles at different weight percentage (0 ,4 ,12 and 16) wt%, specifically designed for their infrared (IR) radiation-blocking capabilities. In today's context of increasing demand for effective IR radiation management in applications such as energy-efficient building coatings and thermal control systems, the investigation of these composite coatings is of paramount importance. Accordingly, conducted a systematic study using advanced techniques such as mechanical ,optical and characterization properties.   From the XRD results, pure PVA appears randomly, with no peaks, but when nanoparticles are added, the crystallinity increases clearly. The results of the adhesion strength of the polyvinyl chloride coating without any additives also showed weak adhesion resistance. When grafted with NPs (CdS or ZnS), the resistance gradually increases. .Micro hardness results display ZnS would likely have higher micro hardnesscompared to CdS. This is because ZnS has smaller particle size compared to CdS and results of scratch show addition of NPs to PVA can enhanced scratch hardness under 0.5 kg load as a compare with pure PVA. The scratch hardness of the prepared samples also increases with the addition of ZnS and CdS to PVA, which leads to enhanced scratch hardness under a load of 0.5 kg compared to pure PVA. Two PVA/NPs composites, 4% PVA/ZnS and 4% PVA/CdS, were investigated for radiation shielding in the study; the latter demonstrated greater shielding than the former. The PVA/CdS composite has the potential to filter infrared radiation more effectively because of the semiconductor material's ability to absorb and reflect infrared radiation, increasing its overall infrared blocking capacity. Both composites effectively shielded radiation when compared to the atmospheric value.